Analysis Of Factors Affecting The Premature Labor - Retno Sari Kartikawati (Journal for Quality in Public Health, 2019)
Premature labor or Parturition Prematurus is labor that occurs at a gestational age of less than 37 weeks, which is calculated from the first day of last menstruation. The cause of death of infants and toddlers is a problem that occurs in newborns / neonatal (0-28 days). Where problems in neonatal include: asphyxia, LBW, and infection. Premature infant deaths that occur at less than 32 weeks' gestation can cause death as much as 15 to 75 times more than babies born at term.This type of research is quantitative observational analytic cross sectional approach. This study was conducted from September 24 to October 24, 2018 in the District Hospital of Mojokerto with a population of 312 women. The sample size is 104 respondents. The independent variables are age, stress of pregnant women, parity, nutrition of pregnant women, anemia. The dependent variable was preterm labor at gestational age <37 mg and normal labor at gestational age> 37 mg. Data were collected using a questionnaire. Data were analyzed using logistic regression test with α = 0.05